Políticas públicas, financiamento e democratização da educação superior: avaliação do REUNI da Universidade Federal o Tocantins - Melo, Nara Poliana de Souza Bandeira de (2011)
In this text, as qualitative and quantitative perspective, the goal is an evaluation the REUNI at the University of Tocantins, Campus of Palmas. The program makes up the policy of expansion and democratization of higher education. The literature up titles that still discuss the democratization of higher education, evaluation of public policies in Brazil and the political and economic context in which they gave the expansion of higher education in recent decades. The way chosen articulated quantitative and qualitative data in favor of performing a thorough evaluation of the program. Thus, data were collected economic, political and cultural state of the Tocantins and the Federal University of Tocantins and the implementation of the program at the institution. Were also conducted archival research and interviews with managers, teachers and students at the UFT, in order to reconstruct the trajectory of the program at the institution. The study shows there are different conceptions of the REUNI and its implementation in the UFT was not a consensus. The concept of democracy present in the gathered within the institution is placed with a focus on access, disregarding the need to guarantee permanence. The study allowed us to verify that funding for the proposed expansion is not proportional to the activities implemented and did not consider the existing deficit in the universities. The field research also involved the lifting of the socio-economic profile of students in courses created from the REUNI. The universe of 62 students who answered the questionnaires, the data revealed that students are mostly young, single, not living with the family, come from public school and have family income of up to three minimum wages. To collect data on the profile of these students, open interviews were conducted with ten students among those who answered the questionnaires. The results showed that reunited the limited period examined, but that reflected a time of expansion in higher education in the UFT, there was a trend towards democratizing of social inclusion and distribution of academic quality independent of